Examining the Impact of Competence and Person–Organization Fit on Organizational Commitment and Employee Performance in a Public Health Center - Gusti Ayu Sintya Ariyati; I Made Sara; Gusti Ayu Sugiati (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2026)
Along with the increasing public demands for the quality of health services, Puskesmas as a first-level health service facility has a strategic role in supporting the achievement of optimal public health degrees. In its implementation, the quality of service is highly determined by the performance of employees as the main implementers of public services. Therefore, organizations need to pay attention to internal factors that can affect employee performance. Based on these conditions, it is necessary to conduct research to analyze the factors that affect the performance of employees at the Klungkung II Health Center. This study aims to analyze the influence of competency and Person Organization Fit (PO-Fit) on organizational commitment and employee performance at the Klungkung II Health Center. This study uses a quantitative approach with a census method of 75 employees. Data analysis was carried out using Structural Equation Modeling based on partial least square (sem-pls). The results of the study found that (1) competence has a significant effect on employee performance, (2) competence has a positive and insignificant effect on organizational commitment, (3) person organization fit (PO-fit) has a positive and significant effect on employee performance, (4) person organization fit (PO-fit) has a positive and significant effect on organizational commitment, (5) organizational commitment has a positive but insignificant effect on employee performance, (6) organizational commitment does not mediate the influence of competence on employee performance, (7) organizational commitment does not mediate the influence of PO-fit on employee performance.